Effect of Liquid Rubber Compound on the Physicochemical Properties of Particle Board from Coconut Frond Powder - Teja Dwi Sutanto; Charles Banon; Bambang Trihadi (UNIB Press, 2022)
Particle board research made from coconut frond powder with various concentration of liquid rubber compound has been done. First particle board was made by mixing 50 mesh of coconut front powder with various concentration of liquid rubber compound there are 25; 30; 35; 40 and 45 % to obtain a particle board with the length, width and height of 5 x 10 x 7.5 cm and then dried by drying. Subsequently the particle board pressed to a thickness of 2.5 cm and then tested the modulus of rupture (MOR), the modulus of elasticity (MOE), the Screw Hold Strength and water absorption. The results indicated that the best condition was obtained on the use of 45 % of liquid rubber compound. In this condition, the value of MOR, MOE, screw hold strength and water absorption are 1436.16 g/ mm2, 2354.38 g/ mm2, 5.2708 N/ cm2 and 41.85% respectively.